Source-to-sink system and sedimentary characteristics of the lower Miocene submarine fans in the eastern deepwater area of the Qiongdongnan Basin, northern South China Sea - Sun, Rui; Yao, Xingzong; Wang, Xiayang; Wu, Keqiang; Han, Yinxue; Xu, Jianyong; Yang, Haizhang; Li, Hongyi; Zeng, Qingbo; Song, Zezhang (Frontiers in Earth Science, 2022)
As the main target of deepwater oil and gas exploration, submarine fans are also the frontier and focus of sedimentology research. Based on the latest three-dimensional (3D) seismic data covering the study area, as well as heavy mineral, rare earth elements, and other data and guided by the theory of seismic sedimentology, this study analyzes the lower Miocene provenance system and sediment dispersion system in the eastern deepwater area of the Qiongdongnan Basin, northern South China Sea, from the perspective of source-to-sink system research. Our research defines the sediment supply function of provenance, paleogeomorphology and valley transport system, sedimentation results and distribution, and the coupling relationship between the source–channel–sink system and comprehensively constructs a set of application guidelines of source-to-sink system research to guide the exploration and prediction of favorable play in the study area and other similar basins. This study shows that in the early Miocene, as controlled by tectonics and paleogeomorphology, uplift areas developed on both the northern and southern sides of the Songnan, Baodao, and Changchang Sags in the Qiongdongnan Basin and small provenances of near-sag uplifts were found in the southern part of the sag. The provenance area in the northern part of the sag was large but not unified, and it formed different provenance systems consisting of the Hainan Uplift in the northern Songnan Sag, Hainan Uplift in the northern Baodao Sag, and Shenhu Uplift in the northern Changchang Sag. A series of canyon systems that developed in the early Miocene were the main channels for sediment transport from the shelf to the slope in the northern Songnan, Baodao, and Changchang Sags. In the early stage of the early Miocene, due to regional sea level decline, the scale of the canyons was generally large, and the scale of the canyons on the northern edge of the Songnan Sag was significantly larger than that of the Baodao Sag. As the relative sea level rose, the canyons became small, narrow, and shallow in the late stage of the early Miocene. Under the dual control of the “source–channel” system, multiple “delta–canyon–submarine fan” depositional systems developed in the Songnan, Baodao, and Changchang Sags in the early Miocene, and large deltas in the depositional systems were mainly located along the northern part of the sag and prograded to the shelf edge of the northern Songnan, Baodao, and Changchang Sags from north to south, providing a good material basis for the development of deepwater sediments.